Prediksi Jumlah Penggunaan BBM Perbulan Menggunakan Algoritma Decition Tree (C4.5) Pada Kantor Dinas Lingkungan Hidup dan Kebersihan Kecamatan Selong Kabupaten Lombok Timur - Yahya, Yahya; Zuliana, Reni (Fakultas Teknik Universitas Hamzanwadi, 2018)
In the world of work or the world of education, even government or public agencies have used sophisticated electronic devices, especially computers. computers are widely used to help human work in completing their work to make it easier and more efficient. Because with our computers can be made easier in making information that is more understood by many people. Besides computers, software (software) is also very necessary in processing a data to make it easier for someone to process their data into more useful data. Environmental and Hygiene Office East Lombok District Selong District is one of the offices that receives fuel subsidies from the central government. Therefore, the prediction using the Decition Tree algorithm (C4.5) in calculating the amount of BBM usage needs to be done in order to optimize the use of BBM as well as possible. Because many officers or individuals are not responsible for cases due to misuse of subsidized fuel. With this prediction, usage can be adjusted optimally and excessive use can be overcome.DOI : 10.29408/jit.v1i1.895